Kelimpahan Zooplankton Berdasarkan Resting Egg pada Sedimen Situ Cijeruk Kabupaten Sukabumi - Maulana Malik; Arif Supendi; Novita MZ; Pelita Octorina (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study aims to determine the potential zooplankton abundance based on resting eggs in situ cijeuk Sukamekar Village Sukaraja sub-district, Sukabumi district. This research was conducted from October to November 2023. October - November 2023. The sampling location was determined by purposive sampling. The research area was divided into 5 sampling points. Data analysis using the abundance formula and the Microsoft Excel 2013 program and a microscope equipped with the scopeImage 9.0 application scopeImage 9.0 application. The results showed the abundance of Resting eggs at 5 observation points ranged from 92 ± 58 - 1009 ± 1206 grains/m², egg diameter ranged from 4.3 ± 0.57 - 7 ± 1 µm, indicating that the presence of resting egg zooplankton in the cijeruk site still has natural food potential and the results of water quality observations at each station with temperatures ranging between 24.33 ± 0.58 - 25.33 ± 0.58ºC, pH 5.08 ± 2.07 - 6.34 ± 0.31, dissolved oxygen1.83 ± 1.29 - 4.70 ± 1.95 mg/l, brightness 27.50 ± 17.26 - 114 ± 25.06 cm.